Physics Teaching and the Development of Reasoning - Dykstra, Jr., Dewey I. (Scientia in educatione, 2013)
Piaget’s theory of cognitive equilibration and research methods sparked the current era in physics education research in the U. S. and other countries. Some of the history of the early development of the physics education research community is described. Essential features of the theory of cognitive equilibration are explained. Piaget and colleagues summarize some 60 years of data collection on children’s reasoning as a series of stages in the development of reasoning. A pedagogy based on the theory of cognitive equilibration and Glasersfeld’s radical constructivism is described. Evidence that people do not make use of formal operations in their reasoning even though college educated is raised as a challenge to the effective function of democratic societies. If it is known how to influence more students to develop further in their reasoning abilities, should this not be an important effort in our educational systems? Should we graduate students from schools and colleges who show no evidence of formal-operational reasoning?